Text analytics APIs, Part 2: The smaller players. (1st August 2018) - DALE, ROBERT
Abstract: It seems like there's yet another cloud-based text analytics Application Programming Interface (API) on the market every few weeks. If you're interested in building an application using these kinds of services, how do you decide which API to go for? In the previous Industry Watch post, we looked at the text analytics APIs from the behemoths in the cloud software world: Amazon, Google, IBM and Microsoft. In this post, we survey sixteen APIs offered by smaller players in the market.